Obesity and gynecological cancer - Galdos Kajatt, Oscar (2025)
Obesity is a growing public health problem and its association with some chronicdiseases, including some types of cancer, mainly breast cancer and endometrialcancer, is increasingly clear. In this review we analyze some mechanisms of thisrelationship, such as: aromatization in fatty tissue, insulin resistance, chronicinflammation and immune dysfunction.